Evaluating the impact of microcredit on poverty prevalence in Sub-Saharan Africa - Sarkodie, Eric Effah; Maloma, Ismael (Asian Economic and Financial Review, 2025)
This study investigates the impact of microcredit on poverty prevalence in SSA. The study adopts a panel regression framework assisted by the generalized method of moments to analyze data across 20 SSA countries from 2009 to 2019. The results show that microcredit effectively diminishes headcount poverty, primarily due to its long-term sustainability when embedded within a wider socioeconomic environment. Income, educational levels, loan terms, and the level of agricultural involvement were found to determine the success rate of microcredit programs. Poverty is persistent, indicating the presence of structural hindrances that significantly affect what microcredit can achieve in poverty alleviation through transformation. Although microcredit helps facilitate financial inclusion in the short term, its long-term effectiveness is hampered by a lack of financial literacy and high interest rates relative to access to markets. Addressing poverty in SSA requires more than just microcredit; it must be part of a comprehensive framework that includes education and economic growth. Enhancing financial literacy, modifying loan terms, increasing structural investments in agriculture, improving service delivery through technology, and fostering public-private partnerships will enhance the sustainability and impact of microcredit.